Navigating Issues of Equity in Schools Through Research-Practice Partnerships: Stories From the Field (Routledge, 2025)
This book provides a wealth of rich cases describing how research-practice partnerships (RPPs) in K-12 schools navigate equity in the design and implementation of their projects and shares insightful recommendations for both research-side and practice-side RPP leaders engaged in this work. Chapter authors from both researcher and practitioner communities unpack real examples that illustrate how RPPs conceptualized, conducted, and shared research related to prominent equity challenges in K-12 schools. Chapters also detail specific tensions and challenges – political, methodological, relational – and how to overcome these. Presenting an equity-focused RPP framework, this important volume explores how to cultivate trusting and equitable relationships among partners, prioritize humanity and equity in the identification and articulation of a RPP project topic, center equity goals, and align methodological approaches to equity objectives. This important resource helps aspiring, new, and veteran RRP leaders initiate projects or partner with new collaborators as they develop trusting relationships within university and school settings in order to conduct impactful, equity-oriented research.